2010
DOI: 10.1021/la1011378
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Ion Distribution at the Mica−Electrolyte Interface

Abstract: Local ionic environments within nanometer proximity of a surface play a major role in the interactions which occur there and can be of critical importance in, for example, colloid suspensions, as well as biological function. Such environments often vary significantly from bulk properties, as we show here by the direct imaging of a range of monovalent (Li(+), Na(+)) and divalent (Ca(2+), Mg(2+)) cations distributed at the liquid-solid interface of mica. We image local charge distributions relative to the atomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
118
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(137 citation statements)
references
References 14 publications
17
118
1
Order By: Relevance
“…7). The presence of small kosmotropic ions sitting between the main binding sites has already been reported in previous AFM studies 34 and RAXR experiments have also shown that In each case, a simulation snapshot with semi-transparent water molecules is shown (top) together with the corresponding IDM image (bottom). All the IDM data were acquired with a similar cantilever/tip and in identical operating conditions.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…7). The presence of small kosmotropic ions sitting between the main binding sites has already been reported in previous AFM studies 34 and RAXR experiments have also shown that In each case, a simulation snapshot with semi-transparent water molecules is shown (top) together with the corresponding IDM image (bottom). All the IDM data were acquired with a similar cantilever/tip and in identical operating conditions.…”
Section: Discussionsupporting
confidence: 55%
“…When operated in liquid, AFM is able to investigate solid-liquid interfaces locally, often with atomic-or molecular-level resolution [22][23][24][25][26][27][28][29][30][31] and in the presence of ions [32][33][34][35][36] . Studies allowing a clear and unequivocal identification of single ions within a Stern layer are however still sparse, with little information about the formation, stability and dynamics of adsorbed ions at the nanoscale.…”
mentioning
confidence: 99%
“…This repeat spacing is consistent with the lattice spacing of the underlying mica (0.52 nm) 46 , within experimental error, and with previous studies of the protic IL-mica interface. It is produced by propylammonium cations electrostatically bound to the oxygen triads 47 associated with negatively charged mica surface sites. 33,36,37 are apparent for each system.…”
Section: Resultsmentioning
confidence: 99%
“…This imaging mechanism is illustrated by the similarity of the line profiles (figure 4) with those obtained under low temperature UHV conditions despite the presence of fluid at the interface [53]. The use of larger oscillation amplitudes ( results in not only a reduction in the local force gradient sensitivity [14,28], but also a convolution of the solvation forces with the local tip-sample force leading to a loss of atomic resolution [17,60]. The need for high SNR operation is exemplified by the small amplitudes required in order to obtain true atomic resolution.…”
Section: Hopg Imagingmentioning
confidence: 79%
“…For this hydrophilic surface, water molecules (molecular diameter ~ 2.5 Å [61,62]) are expected to be present at the interface. Previously, imaging with comparable amplitudes allowed for the visualization of dehydrated ions at the mica surface in aqueous solutions whereby the small oscillation amplitude excludes water from the tip-sample gap as described above [17]. Under similar conditions in viscous, ionic liquids, it may be possible to directly measure the charge distribution at the solid-liquid interface [10].…”
Section: Mica Imagingmentioning
confidence: 99%